Cerebrospinal fluid concentrations of vemurafenib in patients treated for brain metastatic BRAF-V600 mutated melanoma. Issue 4 (August 2015) - Sakji-Dupré, Lilia; Le Rhun, Emilie; Templier, Carole; Desmedt, Eve; Blanchet, Benoit; Mortier, Laurent
<x xml:space="preserve">Abstract</x> Anti-BRAF agents, including vemurafenib, have modified the prognosis for patients with melanoma. However, a difference can still be observed between extracerebral and cerebral responses. The aim of this study was to investigate the diffusion of vemurafenib in cerebrospinal fluid (CSF) from patients treated for brain metastatic BRAF-V600 mutated melanoma. Six patients treated with vemurafenib 960 mg twice daily were included. These patients had undergone a lumbar puncture because of suspicions of leptomeningeal metastasis, along with simultaneous blood sampling to measure vemurafenib level. The concentrations of vemurafenib in the CSF and the plasma were measured by high-performance liquid chromatography. The mean plasma and CSF concentrations of vemurafenib were 53.4±26.2 and 0.47±0.37 mg/l, respectively. The mean ratio of the CSF : plasma concentration was 0.98±0.84%. No relationship was found between plasma and CSF concentrations (P=0.8). In conclusion, our preliminary results highlight for the first time a low CSF vemurafenib penetration rate associated with a large interindividual variability in patients treated for metastatic BRAF-V600 mutated melanoma and brain metastases. Further investigations with larger cohorts are required to study the relationship between CSF vemurafenib concentrations and cerebral response.